Evaluation of Olive and Palm Byproducts in Feeding Camels - Mahmoud, A.E.M.; El-Bana, H.M. (Pakistan Journal of Nutrition, 2013)
Metabolism trials were carried out using four mature males of Sudanese camels; Camelius dromedaries to evaluate the nutritive value of date stone (DS) and olive cake (OC), palm leaves (PL) and barley grains (BG) or their mixture. Results indicated that barley grains showed significantly (p<0.05) higher digestibility and nutritive value in all nutrients except for EE and ADF compared with either olive cake or date stone. In addition, DS showed better digestibility in all nutrients compared with OC except for EE digestibility. The ration contained BG plus DS recorded the highest digestibility for DM, OM, CP, CF and NFE. While, the ration contained BG plus OC recorded higher digestibility for NDF and ADF. No significant differences were detected in dry matter intake expressed as DMI g/W0.75 by camels fed different either tested feeds or rations. The water intake increased with animals fed DS being 8.42 L compared with BG and OC being 7.58 and 6.92 L, respectively. Also, results showed that animals consumed the ration contained BG plus DS recorded the highest water intake being 8.33 L. Feeding on BG led up to significant (p<0.05) decrease in pH values compared with other feeds after 3 and 5 h. No significant differences in ammonia nitrogen concentration at 5 h post feeding with all feeds. The BG plus DS mixture gave the lowest concentration of rumen ammonia content at the three times. While, BG with PL mixture showed the highest value of rumen ammonia content at the three times. It could be concluded that date stone and olive cake used to feed camel as substitution of barley grains without any adverse effect.